2021
DOI: 10.3390/jcm10184108
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and Clinical Outcomes in a Cohort of Hospitalized Patients with Sars-Cov-2 Infection and Chronic Kidney Disease

Abstract: The aim of the study was to investigate the role of chronic kidney disease (CKD) on in-hospital mortality and on incident atrial fibrillation (AF) in patients infected with SARS-CoV-2. The incidence of acute kidney injury (AKI) was also investigated. Multivariable regression models were used to assess the association between renal function groups (estimated Glomerular Filtration Rate, eGFR, >60 mL/min, 30–59 mL/min, <30 mL/min) and in-hospital all-cause mortality and incident AF and AKI. A cohort of 2816… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
(35 reference statements)
3
8
1
Order By: Relevance
“…The most common cardiovascular risk factors were hypertension, obesity, diabetes mellitus, smoking history, and history of CVD, which are known to be associated with increased severity of COVID-19 [ 7 ]. Although there are reports of increased incidence of atrial fibrillation in patients with COVID-19, our study found no difference between patients with COVID-19 and controls [ 21 ]. Our study found acute CVDs in COVID-19 had a male patient predominance and increased incidence in Black or African American patients.…”
Section: Discussioncontrasting
confidence: 94%
“…The most common cardiovascular risk factors were hypertension, obesity, diabetes mellitus, smoking history, and history of CVD, which are known to be associated with increased severity of COVID-19 [ 7 ]. Although there are reports of increased incidence of atrial fibrillation in patients with COVID-19, our study found no difference between patients with COVID-19 and controls [ 21 ]. Our study found acute CVDs in COVID-19 had a male patient predominance and increased incidence in Black or African American patients.…”
Section: Discussioncontrasting
confidence: 94%
“…First, these patients were older ( O'Driscoll et al, 2021 ), smokers ( Shastri et al, 2021 ;World Health Organization, 2021 ), and obese ( Zheng et al, 2020 ). Second, their co-morbidities included hypertension ( Bailly et al, 2021 ), diabetes mellitus ( Ando et al, 2021 ;Fried et al, 2021 ), cardiovascular disease ( Nishiga et al, 2020 ), and chronic kidney disease Genovesi et al, 2021 ;Petrilli et al, 2020 ;Sullivan et al, 2022 ;Williamson et al, 2020 ). In addition, poor prognostic laboratory biomarkers were higher in these patients ( D -dimer) , CRP ( Brasen et al, 2021 ), and ferritin ( Deng et al, 2021 )).…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, thromboembolism occurs in spite of the administration of anticoagulant medication (mainly (low molecular weight) heparins), which raised questions regarding the optimal management of these patients [35]. Notably, baseline cardiovascular complications associated with hypercoagulability (e.g., atrial fibrillation or kidney dysfunction) are more prevalent in COVID-19 patients with thrombotic complications which may further contribute to the worsening of hypercoagulability in COVID-19 patients [36]. The overall effect of combined pathologies on hypercoagulability and outcomes in global assays such as the ROTEM needs to be elucidated in further clinical studies.…”
Section: Coagulopathy In Covid-19mentioning
confidence: 99%